Probabilistic Prediction of Gastrointestinal Ischemia after Cardiothoracic Surgery - Stephan, Francois; Facque, Mathilde; Salem, Fares Ben; Picq, Olivia; Imbert, Audrey; Genty, Thibaut; Zins, Marc (The Thoracic and Cardiovascular Surgeon, 2024)
Background Gastrointestinal ischemia (GIisch) is challenging to diagnose in patients after cardiothoracic surgery. Computed tomography angiography (CTA) carries substantial false-negative and false-positive rates. The aim of the study was to evaluate if a combination of readily available variables improves the diagnosis of GIisch after cardiothoracic surgery.Methods This retrospective study included patients receiving intensive care after cardiothoracic surgery. GIisch was confirmed by surgical and/or endoscopic findings. A GIisch prediction score was developed using the Spiegelhalter-Knill-Jones system in a training cohort then tested in a validation cohort (patients without obvious signs of GIisch on CTA).Results The training cohort comprised 125 consecutive patients with suspected GIisch in 2008 to 2019, including 85 with confirmed GIisch. CTA, performed in 92 patients, had a high false-negative rate of 17/60 (28%) and a lower false-positive rate of 7/32 (22%). The score included cardiopulmonary bypass, negatively associated with GIisch, and six variables positively associated with GIisch: intraoperative mean arterial pressure < 50 mm Hg, aspartate aminotransferase > 15 N, lactate increase in 24 hour > 20%, and 3 CTA findings, namely, bowel dilation, bowel wall thickening, and mesenteric vasoconstriction. The area under the receiver operating characteristic was 0.82 (95% confidence interval [CI], 0.51–0.93) in the training cohort and 0.82 (95% CI, 0.68–0.96) in the validation cohort (n = 34 patients). Reliability of the predicted probabilities was greatest for probabilities ≤ 30% or ≥ 70%.Conclusion In patients receiving intensive care after cardiothoracic surgery, GIisch cannot be ruled out based solely on CTA findings. A scoring system combining CTA findings with other variables may improve the diagnosis of GIisch in this population.
Keywords: cardiothoracic surgery; bowel ischemia; computed tomography angiography; mortality; nonocclusive mesenteric ischemia; prediction model development